2007
DOI: 10.1111/j.1539-6924.2006.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Laypeople's and Experts' Perception of Nanotechnology Hazards

Abstract: Public perception of nanotechnology may influence the realization of technological advances. Laypeople's (N=375) and experts' (N=46) perception of 20 different nanotechnology applications and three nonnanotechnology applications were examined. The psychometric paradigm was utilized and applications were described in short scenarios. Results showed that laypeople and experts assessed asbestos as much more risky than nanotechnology applications. Analyses of aggregated data suggested that perceived dreadfulness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
250
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 265 publications
(262 citation statements)
references
References 29 publications
6
250
1
5
Order By: Relevance
“…Siegrist et al, 2007) and is founded on the following core nanoscientific concepts and principles (Table 1): Nanotubes (often 1nm in diameter but thousands of times longer) tend to aggregate into "bundles" due to "sticky" forces of adhesion arising from their extraordinarily high surface area-to-volume ratios. In addition, their high length-to-diameter ratios could be harmful in a similar fashion to the toxic effects of asbestos on the lungs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Siegrist et al, 2007) and is founded on the following core nanoscientific concepts and principles (Table 1): Nanotubes (often 1nm in diameter but thousands of times longer) tend to aggregate into "bundles" due to "sticky" forces of adhesion arising from their extraordinarily high surface area-to-volume ratios. In addition, their high length-to-diameter ratios could be harmful in a similar fashion to the toxic effects of asbestos on the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…The student data consisted of a written pre-and posttest (e.g. Gardner, Jones, Taylor, Forrester, & Robertson, 2010;Jones, Andre, Superfine, & Taylor, 2003) Bainbridge, 2002;Cobb & Macoubrie, 2004;Lin et al, 2013;Siegrist, Keller, Kastenholz, Frey, & Weick, 2007). The closed items were statements that students responded to using a visual analogue scale (VAS) (Funke & Reips, 2012;Mytton & Rumbold, 2011) by marking an "X" on a 10-centimeter line ranging from 0 ("Disagree" or "Beneficial") to 10 ("Agree" or "Risky").…”
Section: Data Collectionmentioning
confidence: 99%
“…Results of a Swiss study examining a broad set of nanotechnology applications, ranging from water sterilization to ammunition, suggest that lay people perceive the various nanotechnology applications differently [64] . More specifi cally, results showed that lay people perceived applications such as food packaging or water sterilization as more dreaded risks than applications that are not related to food products.…”
Section: Public Perception Of Nanotechnologymentioning
confidence: 99%
“…Lay people differ in their acceptance of nanotechnology, and trust seems to be a factor that infl uences how lay people assess nanotechnology applications [64,66,67] . Participants having trust in the industry and in regulatory agencies assessed the nanotechnology application more positively than participants not having trust.…”
Section: Public Perception Of Nanotechnologymentioning
confidence: 99%
“…Calls for more research and more caution in applying nanotechnology (Maynard, 2008) have been made (Faunce, Murray, Nasu, & Bowman, 2008). In an article discussing the differences between laypeople's and experts' perception of nanotechnology hazards, Siegrist, Keller, Kastenholz, Frey, and Wiek (2007) pay special attention to the remarks of reviewers who question the ability of experts to judge the risks of nanotechnology (see Siegrist et al, 2007, p. 60). These authors conclude (like Kampers, 2009) that experts use their technological knowledge, but they explicitly state that they "…do not make any claims about the accuracy of the experts' assessments" (Siegrist et al, 2007, p. 67).…”
Section: Confusing Namesmentioning
confidence: 99%